2018
DOI: 10.1089/jamp.2017.1435
|View full text |Cite
|
Sign up to set email alerts
|

Flow Recirculation in Cartilaginous Ring Cavities of Human Trachea Model

Abstract: The detection of recirculation zones in the cartilage ring cavities sheds light on the particle deposition mechanism and helps explain results from previous studies that have observed an enhancement of particle deposition in models with cartilage rings. These results bring to light the importance of including cartilage rings in experimental, numerical, and theoretical models to better understand particle deposition in the trachea and bronchi. In addition, the results provide scientists and medical staff with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…(21) High drug deposition was expected in the trachea owing to the presence of the cartilaginous rings. The presence of the cartilaginous rings in the trachea was shown to greatly influence air flow and particle deposition, (19,(23)(24)(25)(26)(27) owing to inertial impaction (dominating the particle dynamics) (25,26) and enhanced turbulence levels. (26) Russo et al (25) conducted a numerical study investigating the effect of the cartilaginous rings by comparing airflow and particle deposition in a trachea model with and without rings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(21) High drug deposition was expected in the trachea owing to the presence of the cartilaginous rings. The presence of the cartilaginous rings in the trachea was shown to greatly influence air flow and particle deposition, (19,(23)(24)(25)(26)(27) owing to inertial impaction (dominating the particle dynamics) (25,26) and enhanced turbulence levels. (26) Russo et al (25) conducted a numerical study investigating the effect of the cartilaginous rings by comparing airflow and particle deposition in a trachea model with and without rings.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors found that the effect of the rings did not propagate to bifurcation downstream. Montoya Segnini et al (19) investigated this phenomenon in vitro, using Particle Image Velocimetry and Particle Tracking Velocimetry. The effect of the trachea rings on the airflow and particle recirculation, particularly near the walls, was determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the trachea and main bronchi have undulated walls as a result of the cartilaginous rings [ 26 , 33 ], most research in respiratory fluid dynamics omits these features under the assumption that their effect is negligible. Nevertheless, existing research points to the importance of these small protrusions in both flow structure and aerosol deposition [ 6 , 27 , 33 ]. It is well established that surface roughness can have significant impact on wall-bounded flows [ 16 ], particularly when an adverse pressure gradient (APG), for example, an expansion in the cross-sectional area, is present [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have evaluated the effects introduced by cartilaginous rings have found increased particle deposition [ 33 , 44 ], increased shear over the ring surface [ 14 , 39 ], reduced flow separation in the bifurcation [ 6 ], flow recirculation in the ring cavity [ 27 ], and flow asymmetry into the lungs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%